2021
DOI: 10.48550/arxiv.2110.07148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Denominators in Lusztig's asymptotic Hecke algebra via the Plancherel formula

Abstract: Let W be an extended affine Weyl group, H be the affine Hecke algebra of the corresponding affine Weyl group over the ring C[q, q −1 ], and J be Lusztig's asymptotic Hecke algebra, viewed as a based ring with basis {tw}. Viewing J as a subalgebra of the (q −1 )-adic completion of H via Lusztig's map φ, we use Harish-Chandra's Plancherel formula for p-adic groups to show that the coefficient of Tx in tw is a rational function of q, depending only on the two-sided cell containing w, with no poles outside of a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This generalizes a similar statement for the functions ν → trace (π ν , t w ) proven in [Daw23] and confirms an expectation of Braverman and Kazhdan.…”
Section: Introduction 1the Asymptotic Hecke Algebra and P-adic Groupssupporting
confidence: 90%
See 3 more Smart Citations
“…This generalizes a similar statement for the functions ν → trace (π ν , t w ) proven in [Daw23] and confirms an expectation of Braverman and Kazhdan.…”
Section: Introduction 1the Asymptotic Hecke Algebra and P-adic Groupssupporting
confidence: 90%
“…In this section, we show that matrix coefficients with respect to a basis defined via the idempotents t d,ρ depend in fact algebraically on the unramified character ν. The proof is similar to proof of regularity of the function trace (π , t w ) established in [Daw23].…”
Section: Regularity Of Matrix Coefficientsmentioning
confidence: 62%
See 2 more Smart Citations
“…In [BK18], Braverman and Kazhdan gave an interpretation of J in terms of harmonic analysis, casting J as an algebraic version of C(G ∨ ) I (they also defined a ring J doing the same for the full algebra C(G ∨ )) by defining an map J → C(G ∨ ) I . In [Daw21], the author showed that this morphism was essentially the specialization of φ −1 for q = q, and in particular was an injection.…”
Section: Introductionmentioning
confidence: 99%